Pelatihan Penguatan Ekoliterasi Terintegrasi Profil Pelajar Pancasila Bagi Guru Sekolah Dasar - Permata, Santy Dinar; Oktarianto, Muhammad Lutfi; Nuraini, Ni Luh Sakinah; Camelia, Dwi Irkhamna; Wiranta, Dwi Yoga (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
This community service aims to strengthen the integrated ecoliteracy profile of Pancasila students among elementary school teachers. The implementation of this activity refers to the achievement of SDGs 4 and 13, namely quality education and handling climate change. A series of activities were carried out in the form of training and mentoring. Through this program, the level of understanding of teachers about ecological environmental concerns increased from 50% to 74% as shown by the test results. The methods applied include interactive workshops and also making projects in the form of an integrated ecoliteracy activity book of Pancasila student profiles. This program was implemented for one month in cluster 1 Poncokusumo, Malang Regency involving 50 teachers. The implementation of this activity is expected to create a generation that is not only academically smart but also has a strong character in implementing the values of Pancasila and environmental awareness for sustainable life.